Comparison of children's food and beverage intakes with national recommendations in New York City child-care centres. Issue 13 (10th May 2016) - Dixon, L Beth; Breck, Andrew; Kettel Khan, Laura
Abstract: Objective: The present study compared foods and beverages provided to and consumed by children at child-care centres in New York City (NYC) with national nutrition recommendations. Design: The study used survey, observational and centre record data collected from child-care centres. Food and beverage intakes from two days of observation and amounts of energy and nutrients were estimated using the US National Cancer Institute's Automated Self-Administered 24 h Recall system. Setting: Meal and snack time at 108 child-care centres in low-income communities in NYC. Subjects: Children aged 3–4 years old in classrooms selected by the directors of the participating child-care centres. Results: Foods and beverages provided to and consumed by children ( n 630) met >50 % of the Dietary Reference Intake (DRI) for most nutrients. Intakes of fibre and vitamins D and E were <30 % of the DRI. Foods and beverages provided >50 % of the recommended average daily intake amounts for total grains, fruits and fruit juices, and dairy, but <50 % of the recommended amounts for whole grains, protein foods and vegetables. Intake of oils was below the allowance for energy levels, but foods and beverages with solid fats and added sugars exceeded the limits by 68 %. Conclusions: Providing more whole grains, vegetables and low-fat dairy and fewer foods with solid fats and added sugars may improve children's diet quality when at child-care centres. Centre staff may need training, resources and strategies in order to meet the nutrition recommendations.